Reconceptualising social enterprise in the UK through an appreciation of legal identities. Issue 3 (13th April 2018) - Bull, Mike
Abstract : Purpose: The purpose of this paper is to review current conceptualisations of social enterprise and present a new theoretical model for social enterprise in the UK. Design/methodology/approach: This conceptual paper draws on the rise of social enterprise in the UK context. Social enterprise in the UK emerged around the 1980s, in both political consciousness and as an academic discipline. The paper explores organisational antecedents to develop a conceptual model that prioritises different legal forms of social enterprise in the UK regulatory framework. Findings: In critiquing policy, practitioner and academic publications, as well as the theoretical models that operationalise social enterprise, there are two observations from the literature this paper examines: first, Theories to date have tended to conceptualise social enterprise as a single hybrid form, neglecting a consideration of the various legal identities, ownership and governance types; second, Theoretical models have tended to overlook the cultural, regional and political-economic histories within their conceptualisations. Originality/value: The value and originality of this paper lies in offering a new paradigm in the conceptualisation of social enterprise in the UK. This is a new contribution to knowledge that strengthens an understanding of the field. This paper creates the space to broaden and appreciate ideologically and operationally different hybrid business types of social enterprises that include charitable, solidarity and entrepreneurial type social enterprises.